Analisis Pendapatan Usahatani Cabai Rawit Di Desa Bongo Empat Kecamatan Paguyaman Kabupaten Boalemo - Boki, Hardik Alvo; Pangemanan, Paulus Adrian; Rori, Yolanda Pinky Ivanna (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the income of cayenne pepper farmers in Bongo Empat Village, Paguyaman District, Bolemo Regency. This research was conducted from June to December 2022. This research used 2 types of data, namely primary and secondary data. Sampling using purposive sampling method (intentionally). The population of cayenne pepper farmers in Bongo Empat Village is 67 farmers. The samples used were 20 chili farmers who were harvesting during the research. The data analysis method used in this research is descriptive analysis. The results of this study indicate that the net income of cayenne pepper farmers in Bongo Village, Paguyuman District, Boalemo Regency can be IDR62.361.311 per hectare.